Naturalizing culture—time for an ecological understanding of “culture” in international culture and sustainability policies - Pyykkönen, Miikka (Frontiers in Political Science, 2024)
The current hegemonic understanding of culture and sustainability leans strongly on the conceptualization of ’culture’ as profoundly anthropocentric. ‘Sustainability’ in cultural policies again means often the potential of creative industries in contributing to the economic growth. This approach can be seen very problematic in the era of extending environmental crisis, which urgently calls for not only a new kind of policies on sustainability, but also new thinking on the relation between culture and nature. The main purpose of this article is to analyze how recent theories and concepts concerning the rethinking of nature–culture relationship and ecological citizen-subjectivity could challenge the hegemonic economist sustainability discourse of cultural policies. The article presents the results of discourse analysis on how the economic side of sustainability has recently become the mainstream signification in international cultural policies and what are the major documents and institutions maintaining and strengthening this approach. The discourse analysis focuses on the questions: how the cultural sustainability is systematically signified and what are the arguments and justifications for the main significations the documents make. The data consists of the conventions, declarations and program papers of G20, OECD, UN, UNCTAD, UNESCO and WTO from 2000 until now. Theoretically I go through the key ideas of the novel social theories on the ecologization of economy, society, culture and citizenship/subjectivity as proposed by Tim Jackson, Bruno Latour, Andreas Malm and Planetary well-being research group. I consider how the hegemony of economism and anthropocentrism in cultural policies could be changed with their help.